2009
DOI: 10.1038/cgt.2009.59
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor growth and induction of apoptosis in prostate cancer cell lines by overexpression of tissue inhibitor of matrix metalloproteinase-3

Abstract: The destruction of extracellular matrix by matrix metalloproteinases is a key event in cancer progression. The tissue inhibitors of metalloproteinases can restrain tumor growth by inhibiting these enzymes. We sought to determine whether overexpression of tissue inhibitor of metalloproteinase-3 (TIMP-3) could suppress the malignant phenotype of human prostate cancer cell line PC-3M. Stable overexpression of TIMP-3 inhibited cell proliferation significantly by MTT assay. Both early and late apoptosis were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Because prostate cancer represents an accumulation of genetic mutations in cells that have gone awry, a novel approach against this cancer is gene therapy. 20 Signal transducers and activators of transcription (STAT) proteins are a family of seven proteins (Stats 1, 2, 3, 4, 5a, 5b and 6) that mediate the transduction of extracellular signals to the transcription of target genes. Among the STATs, Stat3 is the most important, being closely linked to tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because prostate cancer represents an accumulation of genetic mutations in cells that have gone awry, a novel approach against this cancer is gene therapy. 20 Signal transducers and activators of transcription (STAT) proteins are a family of seven proteins (Stats 1, 2, 3, 4, 5a, 5b and 6) that mediate the transduction of extracellular signals to the transcription of target genes. Among the STATs, Stat3 is the most important, being closely linked to tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Proteins of interest were detected using Survivin and b-actin antibodies from Santa Cruz Biotech according to the manufacture's protocol. GRIM-19 antibody was applied as before.…”
Section: Western Blottingmentioning
confidence: 99%
“…It is a growth suppressive gene product in the IFN and retinoic acid-induced cell death pathway. 16 Accumulating data has revealed that a GRIM-19 mutation plays a role in the development/progression of thyroid carcinoma plus the low expression of GRIM-19 has been observed in some primary human renal and PCas. 17,18 Accumulating data indicated that most tumors express high levels of signal transducer and activator of transcription 3 (Stat3), which is known to upregulate the expression of Survivin.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] TIMP-3 can inhibit invasion and induce cell apoptosis in some specific cancer cell strains. [18][19][20][21][22] These observations indicate that TIMP-3 expressed within the tumor microenvironment exerts suppressive effects on tumorigenesis and metastatic colonization, mainly because of its antiangiogenic activity. Indeed, the immune system and the inflammatory factors have been reported crucial in regulation of angiogenesis.…”
Section: Introductionmentioning
confidence: 96%